2005
DOI: 10.1007/s00227-005-0128-9
|View full text |Cite
|
Sign up to set email alerts
|

How an introduced seaweed can affect epibiota diversity in different coastal systems

Abstract: Invasions by non-indigenous species have the potential to alter the biodiversity of recipient systems. The magnitude of this effect often depends on the nature of the invaded communities and the ecology of the invader. We investigated the impacts of the Japanese seaweed Sargassum muticum (Phaeophyceae, Fucales) on biodiversity in a rocky and sedimentary environment on two islands in the North Sea. In each case, we compared the epibiota of non-indigenous S. muticum with epibiota communities on taxonomically rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 50 publications
3
92
2
Order By: Relevance
“…Communities supported by ecosystem engineers are typically specific to the created habitat, such as mussel or kelp beds, oyster reefs and seagrass meadows, because of the innate differences between the foundation species (Buschbaum et al, 2006;Hosack et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Communities supported by ecosystem engineers are typically specific to the created habitat, such as mussel or kelp beds, oyster reefs and seagrass meadows, because of the innate differences between the foundation species (Buschbaum et al, 2006;Hosack et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Since the growth of Sargassum muticum in the Wadden Sea is pseudo-perennial, the algal biomass decreases drastically during late summer and early fall, when lateral branches detach (Jephson & Gray 1977, Buschbaum et al 2006. Therefore, S. muticum habitats are only temporarily available and do not support a resident fish fauna.…”
Section: Discussionmentioning
confidence: 99%
“…However, depending on the capacity of ecological niches in the receptor system, it is also possible that introduced, habitat-forming organisms may promote the diversity of native communities instead of harming them. Buschbaum et al (2006) found 60 species of epibionts associated with Sargassum muticum in the Wadden Sea, and a high number of them were originally rare in the area. However, there is also evidence of negative effects, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations